CUSTOMER LOYALTY, THROUGH CUSTOMER SATISFACTION IN CUSTOMERS PT. XYZ - Dewi, Liliana (Jurnal Aplikasi Manajemen, 2020)
PT. XYZ is one paper company in East Java, Indonesia. The paperÂ  industry grows much wider opportunities to consumers to help select and purchase the product in accordance with the wishes and needs. This resulted in the emergence of competition between paper companies. Consumer expectations this time are getting a good paper and an affordable price, if these expectations are fulfilled then the customer will feel satisfied and by itself will refer to the paper company. PT. XYZ as the paper industry players feel that the best service quality to consumers is essential. The type of research used is applied research. The nature of this research is explanatory research which aims to determine the effect of service quality consisting of tangibility, reliability, responsiveness, assurance, and empathy to customer satisfaction and determine the effect of customer satisfaction on customer loyalty. This study determines the number of respondents 10 times the number of indicators (= 12 indicators) that is 120 respondents. The sample used in this study is a paper distributor that takes directly from the company PT XYZ in Surabaya. This research uses Path Analysis.There were 125 questionnaires distributed and those that met the requirements established 120 questionnaires. The sample used in this study is a paper distributor that takes directly from the company PT XYZ in Surabaya. Based on this research, it proved that the factors of service quality consisting of tangibles, reliability, responsiveness, assurance, and empathy affect consumer satisfaction PT. XYZ, so the first hypothesis can be accepted. AMOS calculation results can be seen from the path coefficient of 2.468 was obtained with CR values of probability of significance is 0.014. The hypothesis was accepted with immediate effect from the factor of service quality on customer satisfaction by 0.602. Good service quality can give satisfaction to the consumer, but not necessarily lead to a loyal customer following consumer satisfaction. Based on the findings proved consumer satisfaction is not proven to influence consumer loyalty to the product of PT. XYZ, so that the second hypothesis was rejected. The path coefficient of 1.535 was obtained with CR values of probability of significance is 0.125. A hypothesis is rejected with a direct influence on customer loyalty on customer satisfaction by 0.202.